Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Les Petits et les Grands amis : Faciliter des échanges et développer des attitudes favorables entre les générations en milieu minoritaire. - de Moissac, Danielle; Arbez, Dominique; Alper, David; Bourrier, Patricia (Université de Saint-Boniface, 2021)
Dans la francophonie canadienne en contexte minoritaire, la population croissante d’aînés est à risque d’isolement social en raison des effets du vieillissement et du statut linguistique minoritaire. Les aînés vivant avec la démence sont davantage vulnérables à l’isolement, ce qui peut avoir comme conséquence d’aggraver le déclin cognitif et psychologique. D’autre part, la mobilité familiale, en particulier celle des familles immigrantes, fait en sorte que les échanges entre générations sont moins fréquents, tant pour les enfants que pour les aînés. Ce manque d’exposition et d’échanges entre les générations peut avoir un effet sur les enfants et mener à une perception défavorable des personnes âgées. Des études ont démontré que la participation aux programmes intergénérationnels favorise la santé physique et mentale des aînés, ainsi que leur engagement social. Pour les enfants, ces programmes favorisent leurs compétences sociales et émotionnelles et le développement d’attitudes positives à l’égard des aînés. Les programmes visant les aînés avec la démence et les enfants d’âge préscolaire suggèrent une attention particulière aux choix d’activités pour maintenir l’intérêt des deux groupes tout en respectant leurs capacités physiques et cognitives. Un programme intergénérationnel a été mis en place pour pallier l’isolement social des aînés et favoriser le développement d’attitudes positives chez les enfants à l’égard des aînés tout en reflétant la langue et les diverses cultures de la francophonie manitobaine. Une étude a été menée, ayant comme objectifs d’examiner l’impact de cette initiative sur le sentiment d’isolement social des résidents aînés d’un foyer de soins de longue durée et la perception des enfants quant aux aînés. Un programme intergénérationnel comprenant 8 séances d’activités a eu lieu à l’automne 20 9 au foyer de soins de longue durée dans un espace permettant aux enfants et aux aînés de participer à des activités de grand rassemblement et des activités en petits groupes. Les enfants du service de garde éducatif se déplaçaient une fois par semaine pour y participer. Des entrevues semidirigées ont été effectuées avant et après le programme intergénérationnel auprès ) des enfants, pour qualifier leur perception des personnes âgées et 2) auprès des aînés, en ce qui a trait à leur réseau social et leur sentiment d’isolement. De plus, les parents/ tuteurs des enfants participants ont été invités à compléter un questionnaire sur l’expérience de leur enfant auprès des personnes âgées avant les sessions intergénérationnelles. Les enfants participants ont pu créer des dessins commentés représentant leurs expériences avec les aînés à la suite de leur participation aux sessions intergénérationnelles. De plus, des observations ont été faites par des assistants de recherche lors des séances d’activité. Quelques membres du personnel du foyer de soins de longue durée et du service de garde éducatif ont également rempli un questionnaire d’évaluation de l’activité intergénérationnelle. Ainsi, l’ensemble des perspectives nous a permis de mieux saisir les effets des échanges intergénérationnels sur les participants.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada